REDUCING THE WORKPLACE ACCIDENT RATE ON THE ENDLESS MACHINE USING JOB SAFETY ANALYSIS (JSA) AND HIRADC IN THE CHAIN 2 WHEEL DEPARTMENT OF PT DAIDO MANUFACTURING INDONESIA - Melisa Meilani; Hendi Iskandar; Tarman (FEBI UIN Sunan Gunung Djati Bandung, 2026)
Occupational accidents remain a persistent problem in manufacturing lines that depend on high-speed mechanical equipment, and the automotive chain assembly industry is no exception. This study examined the Endless machine in the Chain-2-Wheel Department of PT Daido Manufacturing Indonesia, the production stage that recorded the highest number of workplace accidents between January and June 2024. A descriptive qualitative case-study design was applied, combining direct observation, in-depth interviews, documentation review, and literature study. Hazard identification and risk evaluation were carried out through an integrated Job Safety Analysis (JSA) and Hazard Identification, Risk Assessment and Determining Control (HIRADC) framework, supported by Fishbone diagram analysis to trace the root causes. Ten work activities with varying risk levels were identified, three of which were classified as high risk: chain installation into the machine, pin pressing, and machine-area cleaning. Manpower and work-method factors were found to be the dominant root causes. Following the implementation of safety briefings, competency evaluation, and periodic SOP review, the number of accidents declined from seven cases in the baseline period to two cases in the transition period, and to zero cases afterward. These findings confirm that an integrated JSA-HIRADC approach can substantially reduce occupational risk on high-speed mechanical equipment.